Evaluation of an improved rapid bacterial assay with untreated and pathogen‐reduced platelets: Detection of Acinetobacter strains. Issue 9 (27th May 2021) - LaVerda, David; Shinefeld, Lisa; Best, Nancy; Lisitu, Johny; Tambolleo, Gary; Vallejo, Yli Remo
Abstract: Background: The PGD prime ® test was updated to enable Acinetobacter spp. detection to respond to morbidity and mortality events in 2018 and 2020 involving platelets contaminated with Acinetobacter‐calcoaceticus‐baumannii complex ( ACBC ). In one morbidity event, the first‐generation PGD test failed to detect ACBC . In two other reported events, pathogen‐reduced (PR) platelets contaminated with ACBC and other bacteria led to patient morbidity and one death. Study Design and Methods: A polyclonal antibody to Acinetobacter was integrated in the test device and evaluated for detection of Acinetobacter spp., including the ACBC isolate recovered in one of the 2018 contamination events. Limits of Detection for various Acinetobacter strains were determined in dilution studies. Detection of Acinetobacter growing in platelets after an initial low inoculum was evaluated. Use of the updated test as a secondary test after pathogen reduction was also evaluated by testing at 12‐h intervals PR platelet units inoculated with low levels of the 3 species reported in the fatal PR platelet: ACBC, Staphylococcus saprophyticus, and Leclercia adecarboxylata . Results: The test detected several Acinetobacter strains at the clinically relevant CFU/ml levels associated with septic transfusions and successfully detected Acinetobacter growing in various non‐PR platelet types after an initial low inoculum. In PR platelets, the test yielded a positive result with the 3 implicated bacteria in 48 h or less after inoculation, or 48–72 h earlier than the reported time of transfusion of contaminated PR platelets. Conclusion: PGD prime was improved to detect Acinetobacter and has shown utility to interdict contaminated PR platelets.